Psychometric Properties of the Emotional Exhaustion Scale for Children and Adolescents (Ees-Ca) - Barahona-Fuentes, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Emotional exhaustion in children and adolescents has become a significant concern in post-pandemic educational settings, with increased risks of anxiety, depression, and academic disengagement. Despite the growing prevalence of burnout symptoms in school-aged populations, few psychometrically validated tools exist to assess this construct in younger cohorts. This study aimed to validate the factorial structure and psychometric properties of the Emotional Exhaustion Scale (EES-CA) for use in children and adolescents, focusing on reliability, internal structure, and convergent validity. An instrumental, cross-sectional study was conducted with a sample of 543 Chilean students aged 10 to 18 (M = 13.00, SD = 1.77). The EES-CA, adapted from the university-level Emotional Exhaustion Scale, was administered along with the Depression, Anxiety, and Stress Scale (DASS-21). Data were analyzed in the following four phases: descriptive analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and convergent validity. Reliability was estimated via Cronbach’s alpha and McDonald’s omega. EFA supported the following two-factor solution: Scholar Stress and Emotional Fatigue, explaining 58.49% of the total variance. CFA confirmed the superiority of the bifactorial model (χ2 = 91.74, df = 34; CFI = 0.960; RMSEA = 0.072) over the unifactorial model (χ2 = 133.20, df = 35; CFI = 0.932; RMSEA = 0.093). The internal consistency was strong (α = 0.888; ω = 0.883). The convergent validity for the EES-CA showed low correlations with wellbeing (PWI) and non-significant correlations with emotional intelligence (TMMS-24), supporting discriminant validity. The EES-CA exhibits a robust bifactorial structure with high reliability and valid associations with psychological distress measures. This scale is an appropriate and psychometrically sound instrument for assessing emotional exhaustion in school-aged populations, providing a valuable tool for early detection and intervention in educational and mental health contexts. © 2025 by the authors.